Crown status of holm oak (Quercus ilex L.) trees as related to phenology and environmental stress - Bussotti, F.; Ferretti, M.; COZZI, A. (Water, Air, & Soil …, 1995)
In order to study the possible interactions between air pollution and climate coaditions in Mediterranean evergream broadleaf species, since 1987 we have been monitoring the annual and infra-annual variations in crown density of Quercus ilex L. (holm oak) in a permanent sample plot. The behaviour of crown density has been compared with litterfall pattern and aging processes in leaves. The results of this study confirm the important impact of climate on crown condition in Meditea-raneeaa broadleaves, so that even the role of non- acute pollution can be disguised. Xeromorph adaptations in holm oak leaves are also a mechanism providing a greater protection against poltutants.
Keywords: abscission; crown condition; holm oak (voyant); leaves

CROWN STRUCTURE MODIFICATIONS IN RELATION TO AIR-POLLUTION - Bussotti, F.; BROGI, L.; Grossoni, P.; COZZI, A.; GELLINI, R. (LANDSCAPE AND URBAN PLANNING, 1993)
Analysis of crown structure and crown modifications plays a role of primary importance in surveys of `new types of forest damage', since it is a decisive parameter in assessing the health status of a tree. Several forms of ramification alterations have been described in central and northern European species (Norway spruce, beech, Durmast oak, English oak, birch). This study examines the situation in Tuscany and offers a description of the alterations found in the main species typical of the Mediterranean region (Turkey oak, pubescent oak, holm oak, stone pine). The article discusses the potential impact of these alterations on the most typical forest formations, the ones which characterize the Tuscan landscape, and it describes the modifications already under way.
The following values have no corresponding Zotero field: pub-location: PO BOX 211, 1000 AE AMSTERDAM, NETHERLANDS publisher: ELSEVIER SCIENCE BV
Keywords: crown structure; forest formations; Mediterranean